Lactide and lactic acid oligomer solubility in certain solvents; Petroleum and Coal; Vol. 58, iss. 5 - Glotova V. N. Valentina Nikolaevna; Bikmullina T. N. Tamara Nikolaevna; Lukjyanov A. E. Aleksandr Evgenjevich; Novikov V. T. Viktor Timofeevich; Pokharukova Y. E. Yuliya Evgenjevna (2016, 2016)
Title screen